PENGEMBANGAN MATERI KECERDASAN SPIRITUAL SISWA - Rizki Mulyani; Tri Umari; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to develop spiritual quotient materials class X SLTA/MA equals, and a description of its feasibility in terms of aspects of clarity, systematics, image support, freshness, completeness of the material, and support for video or games. Type of research is the development of data analysis techniques using data validity. The source of the data obtained from the supervisor 1, supervisor 2, three teachers BK, and 30 students of class X.7 SMA NEGERI 4 Pekanbaru. The results showed that the material has been developed spiritual quotient with all aspects of yhe quality of the material is “good”. So that the material is fit for use by teachers guidance and counseling in schools.Key Words: spiritual quotient